Sirt4: A Multifaceted Enzyme at the Crossroads of Mitochondrial Metabolism and Cancer - Tomaselli, Daniela; Steegborn, Clemens; Mai, Antonello; Rotili, Dante (Frontiers in Oncology, 2020)
Sirtuins are NAD+-dependent deacylases that play crucial roles in the regulation of cellular metabolism and, as a result, are implicated in several diseases. The mitochondrial sirtuin Sirt4, for long time considered mainly a mono ADP-ribosyltransferase, recently has shown a robust deacylase activity in addition to the already accepted substrate-dependent lipoamidase and deacetylase properties. Through these and likely other enzymatic and nonenzymatic activities, Sirt4 closely controls various metabolic events and its dysregulation is linked to various aging-related disorders, including type 2 diabetes, cardiac hypertrophy, nonalcoholic fatty liver disease, obesity and cancer. For its capability to inhibit glutamine catabolism and for the modulation of genome stability in cancer cells in response to different DNA-damaging conditions, Sirt4 is proposed as either a mitochondrial tumor suppressor or a tumor promoting protein in a context-dependent manner. In addition to what is already known about the roles of Sirt4 in different biological settings, further studies are certainly still needed in order to validate this enzyme as a new potential target for various aging diseases.